Precision focal-length measurement using imaging conjugates - Liao, Lin-Yao; Braulio de Albuquerque, F. C.; Parks, Robert E.; Sasian, Jose M. (My University, 2012)
A method for effective focal length measurement using imaging conjugates is discussed and demonstrated. This method is used to determine the effective focal length of an objective lens with precision and without the need to know the exact position of the principal planes by measuring relative distances of imaging conjugates. Focal length determination was done with the aid of an interferometer and with a precision of +/- 0.054%. A discussion of the method is presented and an error analysis discussed. This method can be used for characterizing optical systems with a wide range of focal lengths because of its simple experimental configuration. (C) 2012 Society of Photo-Optical Instrumentation Engineers (SPIE). [DOI: 10.1117/1.OE.51.11.113604]
Keywords: focal length; effective focal length; focal length measurement; interferometer; nodal slide